1974
DOI: 10.1149/1.2401832
|View full text |Cite
|
Sign up to set email alerts
|

Interaction Between Phosphosilicate Glass Films and Water

Abstract: Phosphosilicate glass (PSG) films were deposited onto silicon substrates by the oxidation of SiH4 and PH3  at 350°. Densities, phosphorus oxide concentrations, and infrared absorption spectra were measured for the evaluation of the film structure. It was found that nearly all the phosphorus oxide in a PSG film containing more than about 8 mole per cent P2O5 was dissolved into water by exposing to saturated water vapor at 120°C. By heating at elevated temperatures, the phosphorus oxide concentration value… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

1974
1974
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 1 publication
2
30
0
Order By: Relevance
“…͑3͒. This result correlates with experiments by Yoshimaru and Matsuhasi 5 and Nagasima et al 14 In both studies, the water surface concentrations are one order of magnitude higher than ours because their films were exposed to a saturated H 2 O vapor at 120°C. Figures 2-4 show the stress evolutions as a function of storage time for the BPSG, PSG, and USG films, respectively.…”
Section: A Water Adsorption In Cvd Oxidessupporting
confidence: 92%
“…͑3͒. This result correlates with experiments by Yoshimaru and Matsuhasi 5 and Nagasima et al 14 In both studies, the water surface concentrations are one order of magnitude higher than ours because their films were exposed to a saturated H 2 O vapor at 120°C. Figures 2-4 show the stress evolutions as a function of storage time for the BPSG, PSG, and USG films, respectively.…”
Section: A Water Adsorption In Cvd Oxidessupporting
confidence: 92%
“…The water-phosphorous exchange was unexpected, however, it has also been observed in consolidated phosphosilicate glass films used in the semiconductor industry with similar P 2 O 5 content to the KPAS glass. 8 In terms of mechanical performance, hydration strengthening is demonstrated as a viable alternative to ion-exchange strengthening. In fact, it is shown that the KPAS glass with hydration treatment B has considerably higher retained strength and damage resistance than ionexchanged soda-lime silicate.…”
Section: Discussionmentioning
confidence: 99%
“…By measuring the water diffusion rates in an 85 • C and 85% relative humidity (RH) environment for a series of ternary alkali aluminosilicate glasses (70 mol% SiO 2 , 10 mol% Al 2 O 3 , and 20 mol% R 2 O, where R = Li, Na, or K), it was demonstrated that the potassium-based glass yielded a water diffusion coefficient approximately two orders of magnitude higher than either lithium or sodiumbased glasses. 6 Since phosphorous doping of silica glass has also been shown to facilitate hydration, 8 a substitution of 10 mol% P 2 O 5 for SiO 2 was then made in the potassiumcontaining aluminosilicate glass. 6 The diffusivity of water increased another two orders of magnitude such that a 25 μm deep water-containing layer was produced in 65 days in the 85 • C and 85% RH environment.…”
Section: Introductionmentioning
confidence: 99%
“…We have also modeled mechanical solicitations corresponding to the absorption/evaporation of molecules or chemical compounds. In PSG or BPSG, water is absorbed; 28,29 in silicate and siloxane SOG oxides, solvents evaporate during film curing; 30,31 in hydrogen silsesquioxane ͑HSQ͒ SOG silicon dioxide and low-pressure chemical vapor deposition ͑LPCVD͒ silicon nitride, hydrogen evaporates during annealing; [32][33][34] and in LPCVD-TEOS and high density plasma ͑HDP͒ silicon dioxides, OH radicals evaporate. 35,36 Assuming that the diffusivity of the molecules is uniform in the material ͓DϭD 0 exp(ϪE D0 /KT)͔, a Laplace equation is solved to calculate the distribution of the absorbed/evaporated compound.…”
Section: Mechanical Modelsmentioning
confidence: 99%